Solusi Modal Usaha Bagi Umkm - Devianti Safira; Azwani Aulia; Elok Faiqoh Himmah; Aravina Auliya; Lita Permata Umi (Jurnal Bhakti Karya dan Inovatif, 2024)
This community service activity aims to provide practical solutions to address the funding challenges often faced by MSMEs (Micro, Small, and Medium Enterprises). Based on initial surveys and observations, many MSMEs struggle to grow their businesses due to a lack of capital, knowledge about business development, product innovation, and the use of digital marketing. This activity provides training to MSMEs on solutions for obtaining business capital through several alternatives, such as using personal savings, peer-to-peer lending, pawning assets, seeking investors, and government loans. The training is expected to help MSMEs improve their access to business capital, develop their businesses, and remain competitive in the market. The results of the activity showed an increase in participants' understanding of capital access and business development strategies. Evaluation was carried out through quizzes and discussions to assess the success of the training. This activity is expected to provide long-term benefits for MSMEs in managing their businesses.